Ostranenie: On Shame and Knowing - Bowker, Matthew H. (Book collections on Project MUSE., 2020)
Ostranenie, the term for defamiliarization introduced by Russian writer and critic Victor Shklovsky, means, among other things, to see in strangeness. To see in strangeness is to participate in an illusion that is more real than real. It may be achieved by (re)presenting the surface as the substance, the play as the thing, or by examining (from exigere: to drive out) what is present before one's eyes. Ultimately, ostranenie means confessing one's complicity in making known what is known.M.H. Bowker's Ostranenie: On Shame and Knowing is a meditation upon the moment of a mother's death: a moment of defamiliarization in several senses. The body of the work consists of footnotes which elaborate, by exegesis, by parataxis, and sometimes by surprise, the intimate and often hidden relationships between parent and child, illusion and knowledge, shame and loss. These elaborations raise questions about the power of the familiar, the limitations of discursive thought, and the paradoxical nature of the interpersonal, political, and spiritual bargains we make for the sake of security and freedom. Ostranenie treats the personal relationship between the author and his mother in both direct and oblique ways. In a candidly unsettled examination of this relationship and its influence upon the reflections and concerns of the author, the reader is invited to experience a family, a disintegration, a psyche, and its defamiliarization, from the perspectives of both an adult and a child.